Dietary Quality and Ultra-Processed Food Intake in Relation to Metabolic Syndrome - Aryanti Setyaningsih; Yanesti Nuravianda Lestari; Refani Alycia Kusuma; Safira Chairani Dimarti; Muhammad Mukhlis Saputra; Nuzulia Nur Kurniawati; Andriany Purnaningrum; Safna Afifa Putri (Indonesian Journal of Human Nutrition, 2026)
Metabolic syndrome is a growing public health concern in Indonesia. The rising prevalence, which reached 21.66% in 2019, is closely linked to a shift toward imbalanced diets and increased consumption of ultra-processed foods (UPFs) driven by globalization. This study aimed to explore the association between dietary quality and ultra-processed food consumption as risk factors for metabolic syndrome among adults in Kedungmundu, Semarang. This quantitative study used a cross-sectional design and was conducted from January to May 2025 in Kedungmundu, Semarang. A total of 75 adults aged 26-45 years were recruited using purposive sampling. Dietary quality was evaluated using the Diet Quality Index-International (DQI-I), while UPF consumption frequency was assessed via interviews utilizing a modified Food Frequency Questionnaire (FFQ). Metabolic syndrome diagnosis adhered to the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) criteria. Data analysis involved univariate and bivariate techniques, including the Mann-Whitney U test and the Chi-square test. Metabolic syndrome was identified in 38.7% of respondents, with hyperglycemia, low HDL cholesterol, and central obesity. Approximately 53.3% of respondents had a low diet quality score, and 46.7% reported frequent UPF consumption. Diet quality was associated with metabolic syndrome (p=0.031), whereas intake of ultra-processed foods was not significantly associated (p=0.229). Low diet quality was significantly associated with metabolic syndrome, whereas frequent intake of ultra-processed foods was not among adults in Kedungmundu, Semarang.